Molecular cloning, expression of, and regulation by thyroid‐hormone receptor α A in the half‐smooth tongue sole Cynoglossus semilaevis during metamorphosis. Issue 5 (8th March 2016) - Zhang, W. T.; Liu, K.; Xiang, J. S.; Zhang, L. Y.; Liu, W. J.; Dong, Z. D.; Li, Y. Z.; Li, H. L.; Chen, S. L.; Wang, N.
Abstract : To elucidate the effect of thyroid hormone receptor α A ( thraa ) on metamorphosis, the full length cDNA of half‐smooth tongue sole Cynoglossus semilaevis was cloned. The relative gene transcript level of thraa at different development stages was quantified using real‐time PCR. Transcription of thraa increased and declined rapidly during metamorphosis. Hyperthyroidism was induced in juveniles and larvae with exposure to T3 and T4, and hypothyroidism with thiourea (TU), 2‐mercapto‐1‐methylimidazole (MMI). thraa mRNA was higher in fish treated for 6 days with MMI than in untreated controls, although inhibited larvae did not complete metamorphosis. The addition of exogenous T4 reversed this effect in the MMI‐treated group, but not in the TU‐treated group. In situ hybridization revealed progressive tail end of body growth and change during developmental stages, with corresponding changes in thraa expression. This process may be induced by thyroid hormones with thraa as a major mediator. The morphological changes of tip of the tail may be associated with the development of lateral swimming.